2021
DOI: 10.1111/jfpe.13810
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics of food materials in infrared radiation drying: A review

Abstract: In recent years, many infrared (IR) and IR-assisted drying methods such as IR-hot air, IRvacuum, IR-microwave, and vibration aided IR-dryer have been reported for drying of food materials due to its rapid drying behavior and less processing time due to high drying rate, consumes less energy, offers better control over temperature, superior quality products, less ecological footprint and also easily it can be combined with other modes of heating technologies. The combination of IR radiation with other drying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 106 publications
1
45
0
6
Order By: Relevance
“…Table 3 lists the activation energy values of the cantaloupe slices and other agricultural products during infrared and infrared-assisted drying. As presented in Table 3, the Ea value of the cantaloupe slices was consistent with the activation energy of most infrared dried food and agricultural products ranging from 12 to 70.2 kJ/mol [38]. Activation energy represents the energy required to remove moisture from the inside to the outside of the material, which is related to the specific surface area, structural properties and tissue components of the product.…”
Section: Effective Moisture Diffusivities and Activation Energysupporting
confidence: 75%
“…Table 3 lists the activation energy values of the cantaloupe slices and other agricultural products during infrared and infrared-assisted drying. As presented in Table 3, the Ea value of the cantaloupe slices was consistent with the activation energy of most infrared dried food and agricultural products ranging from 12 to 70.2 kJ/mol [38]. Activation energy represents the energy required to remove moisture from the inside to the outside of the material, which is related to the specific surface area, structural properties and tissue components of the product.…”
Section: Effective Moisture Diffusivities and Activation Energysupporting
confidence: 75%
“…IR absorbed by food material penetrates into foods and creates vibration in water molecules and thus generates rapid internal heating at surface and inner layer instantaneously, which increases the water vapor pressure inside food material and increases the temperature on the surface. Therefore, the higher drying rate was observed (Delfiya et al, 2021). In the literature, no study on pear drying of ultrasound‐assisted vacuum drying has been found.…”
Section: Resultsmentioning
confidence: 99%
“…Effective diffusion is an essential feature in modeling the drying process of food and other materials. Being aware of the moisture penetration coefficient is necessary for the process design, quality control, storage issues, and how to move products properly (Delfiya et al, 2021). Fick's second law is widely used to describe diffusion in the drying process of agricultural products (Mohammadi et al, 2019).…”
Section: Determining the Effective Moisture Diffusivitymentioning
confidence: 99%